2015
DOI: 10.1039/c4sc03775h
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon sensitive protecting groups operating via intramolecular electron transfer: uncaging of GABA and tryptophan

Abstract: We present a modular approach to photo-labile protecting groups based on photoinduced electron transfer, providing high sensitivity to two-photon excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 60 publications
(29 reference statements)
2
60
0
Order By: Relevance
“…(b) Two-photon excited photocleavage and uncaging of photolabile protecting groups: (i) two-photon excitation, (ii) dye donates an electron to the release unit, (iii) this unit undergoes a photochemical reaction ending in cargo release. Reprinted from ref 68; copyright 2015, permission from The Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…(b) Two-photon excited photocleavage and uncaging of photolabile protecting groups: (i) two-photon excitation, (ii) dye donates an electron to the release unit, (iii) this unit undergoes a photochemical reaction ending in cargo release. Reprinted from ref 68; copyright 2015, permission from The Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…By combining two 7‐nitroindolinyl (NI)‐caged glutamates with a hydrophilic quadrupolar tailored 2P chromophore, we prepared triads affording a tenfold greater 2P‐induced release of glutamate ( δ u =0.5 GM at 730 nm) in comparison with the parent NI‐protecting group. Pursuing the same goal, triads operating by intramolecular electron transfer have been very recently reported as 2P sensitive protecting groups of amino acids with record 2P uncaging sensitivity . Aiming at further increasing the 2PA ability in the 700–800 nm region and assuming that the presence of a second caging unit within the triad could affect the 2P uncaging efficiency of the overall architecture (due to excitation energy trapping by the cage byproduct), we recently elaborated dissymmetric synergic dyads incorporating a nitroveratryl (NV)‐derived protecting group.…”
Section: Introductionmentioning
confidence: 99%
“…As no charge‐transfer intermediates were detected in laser flash photolysis experiments, neither significant fluorescence was observed, authors suggested that the competing back electron transfer was the main deactivation path that occurred faster than the bond cleavage . Also, a fluorene‐sensitized picolinium derivative sensitive to two‐photon activation has been prepared by the Anderson group . The construct suffered, however, hydrolytic instability and low uncaging efficiency, presumably due to the fast back electron transfer, as was hypothesized in the earlier experiment.…”
Section: Introductionmentioning
confidence: 91%